2021
DOI: 10.1101/2021.01.10.21249533
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of surgical masks on droplet and aerosol dispersion under various oxygen delivery modalities

Abstract: RationaleAerosol dispersion under various oxygen delivery modalities, including high flow nasal cannula, is a critical concern for healthcare workers who treat acute hypoxemic respiratory failure during the coronavirus disease 2019 pandemic. Effects of surgical masks on droplet and aerosol dispersion under oxygen delivery modalities are not yet clarified.ObjectivesTo visualize and quantify dispersion particles under various oxygen delivery modalities and examine the protective effect of surgical masks on parti… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 20 publications
2
4
0
Order By: Relevance
“…Having patients wear surgical masks can reduce the risk of transmission to HCWs ( 13 ). This has been reported in healthy subjects ( 14 ) as well as COVID-19 patients ( 15 ). Reduced dispersion has been confirmed in silica, with computational fluid dynamic simulations reporting that wearing a surgical/procedure mask over HFNC may reduce aerosol droplet dispersion ( 16 ).…”
Section: Introductionsupporting
confidence: 67%
See 1 more Smart Citation
“…Having patients wear surgical masks can reduce the risk of transmission to HCWs ( 13 ). This has been reported in healthy subjects ( 14 ) as well as COVID-19 patients ( 15 ). Reduced dispersion has been confirmed in silica, with computational fluid dynamic simulations reporting that wearing a surgical/procedure mask over HFNC may reduce aerosol droplet dispersion ( 16 ).…”
Section: Introductionsupporting
confidence: 67%
“…Table 3 outlines the average % reduction in aerosol dispersion using a mitigating measure during HFNC reported in previous in vivo studies ( 14 16 , 23 , 24 ) in comparison to this current study using an experimental in vitro model. In contrast to this current study, there were no significant decreases in PNCs with the use of a facemask to mitigate against aerosol dispersion during HFNC at 50 L/min in an in vivo study by Li et al ( 25 ).…”
Section: Discussionmentioning
confidence: 72%
“…Nonetheless, Faraone et al (2021) indicated that the orofacial devices used in non-invasive mechanical ventilation therapies under pressure (CPAP or double pressure levels), or non-mechanical devices such as Boussignac or Pulmodyne CPAP, among others, do not ensure airtightness of the system in any of the cases. These devices were argued against for patients with a high risk of infection, as they represented a risk for the workers’ health (Takazono et al, 2021). Hui et al (2009) measured dispersion of the particles in a piece of equipment that used two different pressure levels with an orofacial mask, finding that it was 0.5 to 0.95 m around the patient through the orifice where the leak took place, and the point where the mask meets the nasal bridge.…”
Section: Discussionmentioning
confidence: 99%
“…Above the pressure of 3 mmHg, and in shearing conditions, the risk of pressure ulcers multiply (Dobler et al, 2020; Gattinoni et al, 2020; Takazono et al, 2021). In any case, as an added complication, facial interfaces do not have systems in place to measure this pressure; therefore, the masks are fitted intuitively, with excessive pressure observed, increasing discomfort.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation